A single test for the determination of the velocity: time-to-exhaustion relationship - Broxterman, Ryan M. (Kansas State University, 2011)
Purpose: To determine if a single test is accurate in determining the parameters of the velocity: time-to-fatigue relationship, i.e., critical velocity (CV) and a finite distance that can be covered above CV (D`). Methods: Ten healthy subjects completed an incremental test to volitional exhaustion followed by four constant-velocity runs on a treadmill for the determination of CV and D`, as well as an all-out 3-minute test on a track for the determination of end-test velocity (EV) and the distance above end-test velocity (DEV). Eight of the eleven subjects completed a second 3-minute test and one run each at (+) and (-) 95% confidence interval velocities of CV determined from the 1/time model. Results: The group mean 1/time model CV (12.8 ± 2.5 km·h[superscript]-1) was significantly greater than the velocity-time model CV (12.3 ± 2.4 km·h[superscript]-1; P < 0.05), while the velocity-time model W` (285 ± 106 m) was greater than the 1/time model W` (220 ± 112 m; P < 0.05). EV (13.0 ± 2.7 km·h[superscript]-1) and DEV (151 ± 45 m) were not significantly different than the 1/time model CV and W`, respectively. EV was greater than the velocity-time model CV (P < 0.05), while the DEV was significantly less than the velocity-time model W` (P = 0.002). No difference was found for group mean EV or DEV between the two 3-minute tests (P > 0.05), which demonstrated a reliability coefficient of 0.85 for EV and 0.32 for DEV. For the CV (-) 95% run, all subjects reached a steady-state in VO[subscript]2, and completed 900 s of exercise. However, for the CV (+) 95% run, VO[subscript]2 never reached a steady-state, but increased until termination of exercise at 643 ± 213 s with a VO[subscript]2peak close to but significantly lower than VO[subscript]2max (P < 0.05). Conclusion: CV can be accurately determined using a single 3-minute test, while W` is underestimated with this protocol.
Keywords: Critical Velocity; 3-minute Test; Running; All-out Test; Kinesiology (0575)